Cholestatic hepatic injury associated with vismodegib, aspirin, and naproxen use: a case study and review of vismodegib safety. (11th July 2014) - Ash, Mark M.; Jolly, Puneet S.
Abstract Background Vismodegib is a novel hedgehog pathway inhibitor approved to treat advanced and metastatic basal cell carcinoma (BCC) in the United States. Several studies have demonstrated efficacy for treatment of new and existing BCC in both basal cell nevus syndrome (BCNS) and non‐BCNS patients. However, severe and numerous adverse events are associated with vismodegib use. Therefore, we have also examined all of the currently published clinical trials and tabulated the available adverse events for review. The most frequently reported adverse events include muscle spasms (53.4%), dysgeusia/ageusia (49.3%), alopecia (38.8%), fatigue (32.0%), nausea (28.4%), weight loss (24.2%), and decreased appetite (16.5%). Case Study We report a case of a previously healthy 72‐year‐old male with a history of innumerable BCCs who developed severe nausea, jaundice, and cholestasis with significantly elevated BUN, creatinine, and liver enzymes one month after starting vismodegib. The patient began using over‐the‐counter nonsteroidal anti‐inflammatory drugs (NSAIDs) to treat severe, vismodegib‐induced myalgia. No other new medications were started. Our patient had no history of liver disease. Conclusions Herein, we describe a potential serious adverse effect associated with vismodegib use. Whether the illness is directly attributable to the medication or the result of drug‐drug interactions between vismodegib and NSAIDs, practitioners should be aware of the possibility of hepatic injury in patients on vismodegib. Furthermore, patients need to be informed of the potential risks of vismodegib and should be monitored closely to ensure that life‐threatening complications of treatment are avoided.